Australian Federalism and the COVID-19 Crisis - Fenna, Alan (Routledge, 2021)
Australia’s federal system handled the COVID-19 pandemic throughout 2020 remarkably well — lauded, indeed, for the unusually cooperative manner in which it functioned (e.g., Saunders 2020; Williams 2020). This was reflected in public opinion, with Australians giving their governments full marks (PRC 2020). There was certainly some friction between the Commonwealth and the States, manifestations of the inevitable tension between the necessity and the cost of prophylactic measures; however, it proved of little detriment.